Marketing Strategy Analysis to Increase the Sales Volume of Fresh Gourami Fish at Bintang Gurame Distributor in Pringsewu, Lampung - Dimastiar Mulia Putra; Defrizal Defrizal (Utan Kayu Publishing, 2026)
This research is focused on the study of applied marketing strategies and identify supporting and inhibiting factors through the integration of the marketing mix (4P) and SWOT analysis. The research approach used is qualitative descriptive, with data collection techniques in the form of observation, interviews, and documentation. The use of SWOT analysis poured into the IFAS and EFAS matrix, based on the results of the analysis, showed that the Bintang Gurame Distributor obtained an IFAS score of 2.92 and an EFAS result of 3.04. These results indicate that the company is in a pretty strong position to take advantage of the opportunities available. Therefore, the implementation of a more aggressive marketing strategy through the SO strategy is the main strategy choice, with the aim of optimizing market opportunities and encouraging a sustainable increase in sales volume.